The Effect of Contextual Teaching and Learning Model Assisted by Video on Students' Learning Outcomes and Motivation - Sari, Ayu Ratna; Gummah, Syifa'ul; Syukroyanti, Baiq Azmi; Habibi, Habibi (Universitas Pendidikan Mandalika, 2024)
This study explores the effectiveness of the Contextual Teaching and Learning (CTL) model, enhanced by video, in improving students' learning outcomes and motivation, specifically in understanding complex physics topics like sound waves. Traditional teaching methods often struggle to engage students with abstract content, creating a need for innovative approaches that bridge theory with practical applications. The CTL model aims to make learning more meaningful by connecting academic material with real-world contexts. A quasi-experimental design with a pretest-posttest control group was employed, involving two randomly selected groups from 50 students at SMAN 1 Masbagik. The experimental group was taught using the CTL model with video assistance, while the control group followed conventional methods. Data collection included learning outcome tests and motivation questionnaires, analyzed using normality, homogeneity, and t-tests to evaluate differences between groups. Results showed that the experimental group achieved a significantly higher posttest average score (78.92) than the control group (74.20), indicating improved comprehension. Additionally, motivation scores in the experimental group averaged 83.5, categorized as